KORPUS LINGVISTIKASIDA «ALIGNER” DASTURLARNING O‘RNI - Xamroyeva, Sh.M.; Matyakubova, N.S. (SCIENCE and SOCIETY, 2023)
Aligners are a crucial tool in corpus linguistics, allowing researchers to automate the process of aligning parallel texts, creating parallel corpora, identifying language patterns, and conducting quantitative analysis. Without Aligners, much of the research in corpus linguistics would be significantly more time-consuming and labor-intensive.